Determinants and outcomes of change in physical activity in COPD - Kantorowski, Ana (ERJ Open Res, 2018)
Determinants of change in physical activity and outcomes of physical activity promotion are unclear. In this secondary analysis of a randomised controlled trial of a physical activity intervention, we assess predictors of change in physical activity and the effects of increasing physical activity on chronic obstructive pulmonary disease (COPD) measures. Physical activity was promoted in 94 subjects with COPD using the Omron HJ-720ITC pedometer alone or the pedometer plus a website that provides goal setting, feedback, motivational and educational messages, and social support for 3 months. We assessed forced expiratory volume in 1 s (FEV(1)), 6-min walk test (6MWT) distance, depression, social support and markers of systemic inflammation (C-reactive protein (CRP) and interleukin (IL)-6). Data from both groups were combined and subjects categorised as responders (increased steps per day) or nonresponders (decreased steps per day). Linear regression models explored predictors of change in physical activity and assessed the effect of response on changes in COPD measures. The cohort of responders (n=62) and nonresponders (n=32) had mean FEV(1) 1.89±0.64 L (63±22% predicted). Baseline steps per day, diagnosis of depression, social support, oxygen use and season significantly predicted change in daily step count. Responders had increases in physical activity (2038 steps per day), FEV(1) (308 mL) and 6MWT distance (43.6 m), and decreases in CRP (7.84 mg·L(−1)) and IL-6 (2.73 ng·mL(−1)) compared with nonresponders (p<0.0001–0.009). History of depression, social support, oxygen use and season predict change in physical activity, and should be routinely assessed in exercise counselling. Increases in physical activity are associated with improvements in lung function, exercise capacity and systemic inflammation.